ENGAGING STUDENTS IN GALLERY WALKS: SENIOR HIGH SCHOOL ENGLISH SPEAKING PROGRAM - Bungah Shallva Almira; Elih Sutisna Yanto (PROJECT (Professional Journal of English Education), 2022)
This article reports the findings of case study research on the deployment of gallery walks in English speaking classroom in the senior high schools in Indonesia. The research use case study design. Drawing on thematic analysis, empirical findings show that the students engaged actively in the topic they are interested and they could work collaboratively through small peer-led discussion. Empirical data also revealed that students could practice speaking through presenting and discussing their topics they chose in front of the class. This empirical evidence supports the use of gallery walks as a procedure in speaking program in purpose in engaging students in collaborative learning through the teacher scaffolding. Three important instructional implications can be drawn from the results of the study. Additionally, gallery walks can be used to engage students in speaking program during discussion and presentation activities. It helps students build their knowledge and speaking ability. Teacher can also bring many variety of topics to make students have more opportunity to explore broaden and deepen topics based on their interests. The future researchers can document the impact gallery walks have on students' speaking fluency and accomplishment in a different context. Keywords:  Engagement, Gallery Walks, Speaking